Volterra Type Integral Operators and Composition Operators on Model Spaces - Tesfa Mengestie (Journal of Function Spaces)
We study some mapping properties of Volterra type integral operators and composition operators on model spaces. We also discuss and give out a couple of interesting open problems in model spaces where any possible solution of the problems can be used to study a number of other operator theoretic related problems in the spaces.